Integrated microbiota and metabolite profiles link Crohn’s disease to sulfur metabolism - Amira Metwaly (Nature Portfolio, 2020)
Gut microbial and metabolite alterations are linked to inflammatory bowel diseases pathogenesis. Here the authors identify functional microbiota signatures that correlate with disease activity by comparing patients with Crohn’s disease undergoing autologous hematopoietic stem cell transplantation who either did not respond to therapy, experienced relapse after remission or maintained remission, and show that these microbial signatures recapitulate disease activity when transferred to mice.